Choice of Delivery Facility among Expectant Mothers in Ghana: Does Access to Health Insurance Matter? - Nketiah-Amponsah, E.; Arthur, E. (Journal of Health Management, 2014)
This article examines the effect of health insurance ownership among expectant mothers on facility-based delivery, having controlled for a host of socio-economic and demographic characteristics. Home deliveries often endanger the health of women, where complications are often referred to appropriate health facilities only when the condition has already deteriorated. Consequently, this study examines the extent to which expectant mothers' access to health insurance influence their choice of delivery facilities broadly categorized into public health facilities, private health facilities and home delivery. Methodologically, the multinomial logistic regression is employed in the empirical estimation. Using the 2008 Ghana Demographic and Health Survey, we found at both the bivariate and multivariate level that women with access to health insurance are more likely to deliver in modern health facilities namely public and private allopathic health facilities relative to home delivery. In particular, women with access to health insurance are approximately 18 percentage points more likely to deliver in a public health facility as compared to home delivery. Also, the propensity to deliver in private health facilities relative to home delivery increases by one percentage point for women with health insurance. Thus, for expectant mothers with health insurance, the utilization of public health facilities predominates. Some of the control variables that were found to significantly influence the choice of delivery facilities include age, educational attainment, wealth quintile, area of residence, religion and region of residence. The study makes a case for scaling up access to health insurance among expectant mothers due to its positive effect on the choice of appropriate delivery facilities. © 2013 Indian Institute of Health Management Research.
Keywords: choice; delivery facility; Expectant mothers; Ghana; health insurance